2013
DOI: 10.1177/1010539513502522
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Community Participation in a Surveillance System Initiative to Prevent Drowning in Thailand

Abstract: This study had a 2-group pre-post quasiexperimental design and was conducted in 2 selected areas of Ubon Ratchathani province, Thailand. The objective was to evaluate the extent to which the surveillance system that was developed helped in drowning prevention. The development process involved extensive participation from the community. System efficiency was evaluated, and the drowning rates were compared. The system demonstrated 82.8% system sensitivity and 87% positive-predictive value. There were 90.0% rescu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…While reducing drowning in low-SDI and middle-SDI countries is a challenge, recent work in Bangladesh34 and Thailand29 39 has demonstrated that country-level commitment and appropriate resourcing to unintentional drowning reduction can have a marked impact on mortality and morbidity rates. A recent review5 of drowning in LMICs found only a small number of studies from LMICs (n=62 studies) which met their inclusion criteria, noting that data used in a third of the included studies were from autopsy and medico-legal records, with the rest from surveys and interviews, hospital records, media and ambulance records.…”
Section: Discussionmentioning
confidence: 99%
“…While reducing drowning in low-SDI and middle-SDI countries is a challenge, recent work in Bangladesh34 and Thailand29 39 has demonstrated that country-level commitment and appropriate resourcing to unintentional drowning reduction can have a marked impact on mortality and morbidity rates. A recent review5 of drowning in LMICs found only a small number of studies from LMICs (n=62 studies) which met their inclusion criteria, noting that data used in a third of the included studies were from autopsy and medico-legal records, with the rest from surveys and interviews, hospital records, media and ambulance records.…”
Section: Discussionmentioning
confidence: 99%
“…1 Developing and administrating evidence-based, risk-awareness education programs designed for village and classroom settings are methods Fiji can explore. [8][9][10] Studies in China and Vietnam have found that the higher the level of safety knowledge the child and parents have on drowning prevention, the less likely the child will be exposed to the risk or behaving riskily. 8,9 Active community involvement from design to delivery further strengthened the success rate of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Active community involvement from design to delivery further strengthened the success rate of interventions. 10 To reinforce key messages, working in collaboration with key media bodies and leading advocates within the high-risk periods may assist in instilling positive behaviors around bodies of water, while heightening the level of proficient supervision of young children. 1 There were several limitations identified in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 At a national or community level, drowning can be prevented through implementing six interventions and four crosscutting implementation strategies. 1 There are a small number of studies reporting the effectiveness of drowning prevention interventions in LMICs, namely from Bangladesh 21 and Thailand, 22 however more work is required.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%